Quill Mites of the Family Syringophilidae (Acariformes: Prostigmata) Associated With the New World and African Parrots (Psittaciformes: Psittacidae) With the Description of Eight New Species. Issue 5 (14th August 2022) - Marciniak–Musial, Natalia; Sikora, Bozena
Abstract: In this paper, we review the quill mite fauna of the family Syringophilidae Lavoipierre, 1953 (Acariformes: Prostigmata) associated with New World and African parrots (Aves: Psittaciformes: Psittacidae), and describe eight new species including: Neoaulobia unsoeldi Marciniak-Musial & Sikora sp. nov. from the Burrowing Parakeet Cyanoliseus patagonus in Argentina; Lawrencipicobia arini Marciniak-Musial & Sikora sp. nov. from the Black-headed Parrot Pionites melanocephalus in Surinam; L . ararauna Marciniak-Musial & Sikora sp. nov. from the Black-headed Parrot Ara ararauna in Brazil; L . touiti Marciniak-Musial & Sikora sp. nov. from the Golden-tailed Parrotlet Touit surdus in Brazil; Rafapicobia valdiviana Marciniak-Musial & Sikora sp. nov. from the Burrowing Parrot Cyanoliseus patagonus in Brazil; R . pyrrhura Marciniak-Musial & Sikora sp. nov. from the Green-cheeked Parakeet Pyrrhura molinae in Bolivia; R . xanthopterygius Marciniak-Musial & Sikora sp. nov. from the Blue-winged Parrotlet Forpus xanthopterygius in Brazil; and R . trainidadi Marciniak-Musial & Sikora sp. nov. from the Lilac-tailed Parrotlet Touit batavicus in Trinidad and Tobago. Additionally, we note fifteen new host species and many new locality records for the previously described taxa, and provide the keys for all species associated with psittaciform birds. Finally, we discuss the host–parasite relationships between syringophilid mites and parrots.